A Multi-Temporal Satellite Data and Spectral Indices for Assessing Spatial Changes in Urban Farmlands in Lagos, Nigeria - Awoniran, Dauda Rotimi; Adeseye, Temitayo Abayomi; Agboola, Shakirulah Olayemi; Babalola, Sunday Oyetayo (The Indonesian Forestry Certification Cooperation, 2024)
To achieve sustainable development for the world’s population food security is one of the environmental existential challenges that must be addressed. This study examined the trend in agricultural land use change, in Lagos Metropolis between 1984 and 2024. Data used included Landsat 5 Thematic Mapper (TM) image of 1984, Landsat 8 Operational Land Imager (OLI) image of 2013 and Landsat 9 (OLI) of 2024. The satellite images were processed using ArcGIS 10.5 and IDRISI Selva software. The processed images were classified using a combination of Normalized Difference Vegetation Indices (NDVI), visual interpretation and Maximum Likelihood Classification algorithm. An inventory of the extent of land use/land cover for each year and the rate of change were determined, the pattern of conversion of urban farmlands to other land uses was also examined, using the Land Use Change Modeller of the IDRISI software. Findings from the study indicated that farmlands in the study area declined by 13.03% between 1984 and 2013 and by 21.79% between 2013 and 2024. So also between 1984 and 2013 as much as 89.48% of farmlands were converted to other land uses, while only 10.52% remained unchanged and between 2013 and 2024 as much as 73.51% had been converted to other land uses, while 26.49 % remained unchanged. Furthermore, the NDVI results indicated a deterioration in the environmental condition of the urban farmlands. The study concluded that the present status of urban farming in Lagos Metropolis has far reaching implications for food security that needed to be addressed.